CLINICAL EVALUATION OF SKIN OF COLOR AND SKIN INTEGRITY MAINTENANCE: AN INTEGRATIVE REVIEW ON HEALTH EQUITY - Rangel Gomes, Shirley; Carlos Do Amaral, Ângela; Aliprandi Lima, Thiago (Health and Society, 2026)
Objective: To analyze current scientific evidence on the morphological characteristics of black skin and discuss how these specificities influence clinical assessment and skin integrity maintenance strategies in nursing practice. Materials and Methods: Integrative literature review conducted in PubMed, SciELO, and LILACS databases, with a temporal cut-off from 2020 to 2025. The selection followed the PRISMA protocol, resulting in 18 analyzed sources (articles and academic works). Results: Black skin presents a more compact stratum corneum, thick dermis with hyper-reactive fibroblasts, and larger, dispersed melanosomes. These features provide UV protection but increase the risk of post-inflammatory hyperpigmentation (PIH) and keloids. It was identified that the Fitzpatrick Scale has limitations in detecting inflammatory erythema (“invisible erythema”), recommending the adoption of technologies such as Alternative Light Source (ALS) and ancestry scales. Conclusion: Maintaining the integrity of black skin requires mastery of ethnodermatology. Professional practice must overcome the Eurocentric standard and institutional racism, integrating sensory and technological methods to ensure health equity and patient safety.